Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/3287733
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites Developed with Litchi Peel Based on Epoxy Resin: Mechanical Properties and Flame Retardant

Abstract: Bio-based composites are reinforced polymeric materials, which include one or two bio-based components. Biocomposites have recently attracted great attention for applications ranging from home appliances to the automotive industry. The outstanding advantages are low cost, biodegradability, lightness, availability, and solving environmental problems. In recent days, biodegradable natural fibers are attracting a great deal of interest from researchers to work on and develop a new type of composite material for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The same can be confirmed from the tensile, compression, and flexural test results. A work reported by Nguyen 25 shows formation of voids at higher filler content in the composites.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 90%
“…The same can be confirmed from the tensile, compression, and flexural test results. A work reported by Nguyen 25 shows formation of voids at higher filler content in the composites.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 90%
“…The scanning electron microscope (SEM) images showed that the grain distribution and adhesion level between lychee bark and epoxy resin were quite good. [24] A.V. Abhijith et al [25] reinforced fabricated composite materials composed of lotus fiber and glass fiber based on epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on making flame retardant materials using nano-additives (nanocarbon, nano clay), fly ash, Graphene Oxide, and natural fibers (used coffee grounds, banana fibers, etc.) by Tuan Anh nguyen and associates have been published in prestigious international journals in SCIE, Q2 [9][10][11][12][13][14][15] . In addition to new contributions to the science of fire prevention and fighting, it also serves training and teaching at Hanoi University of Industry.…”
Section: Introductionmentioning
confidence: 99%